2012
DOI: 10.3109/14017431.2012.663502
|View full text |Cite
|
Sign up to set email alerts
|

Lack of C4d deposition may reveal susceptibility for ascending aortic dissection

Abstract: Lack of C4d may indicate active remodeling of the aortic wall leading to aortic dissection (AD). Immunologic complement factors may be amenable to diagnosis of instability after aortic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Inflammatory conditions of the aorta, including aortitis and vasculitis, may be associated with degeneration of the medial and adventitial layers of the aortic wall [43]. Both immunoglobulin G4 and complement 4d have been reported to be involved in the pathogenesis of aortic dissection [44,45], whereas giant-cell and Takayasu arteritis are associated with a T-cell-mediated inflammation of the vasa vasori, potentially leading to aneurysm formation and fibrotic stenosis of the aorta [46].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Inflammatory conditions of the aorta, including aortitis and vasculitis, may be associated with degeneration of the medial and adventitial layers of the aortic wall [43]. Both immunoglobulin G4 and complement 4d have been reported to be involved in the pathogenesis of aortic dissection [44,45], whereas giant-cell and Takayasu arteritis are associated with a T-cell-mediated inflammation of the vasa vasori, potentially leading to aneurysm formation and fibrotic stenosis of the aorta [46].…”
Section: Risk Factorsmentioning
confidence: 99%
“…This may provide the evidence that the C3-inducing AAAs are not specific, and some proper anti-C3 drugs may work in attenuating the development of AAAs. Another complement component C4d, however, shows a protective role in some inflammatory aortic disease such as aortic dissection [ 65 ].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Although all three pathways of complement are known to be involved in the development of AAA, less is known regarding the potential role of complement in aortic dissection. A previous study suggested that C4d deposition (complement activation) is a predictive marker for susceptibility to ascending aortic dissection (38).…”
Section: Discussionmentioning
confidence: 99%